1989
DOI: 10.1007/bf00999122
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy of biobehavioral and compliance interventions in the adjunctive treatment of mild pregnancy-induced hypertension

Abstract: This investigation assessed the efficacy of a biobehavioral intervention in the adjunctive treatment of mild pregnancy-induced hypertension (PIH), a potentially serious complication of pregnancy in which normotensive women develop hypertension, proteinuria, and edema of unknown etiology late in gestation. Forty-five women with symptoms of PIH were randomly assigned to one of three treatment conditions: bed rest alone (the most common obstetrical treatment), bed rest with individualized compliance enhancement t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 22 publications
0
14
0
Order By: Relevance
“…Interventions through changing the behavioural aspects, like relaxation, adherence to medication, compliance enhancement, bio-feedback techniques, health behaviour practices, exercise, etc., have been carried out to measure its effect on the biological parameters and patho-physical mechanisms (e.g., cardiovascular mechanisms, weight control, cortisol level, immune parameters, etc.). Bio-behavioural interventions have used different behavioural and cognitive nonpharmacologic techniques, like bio-feedback, relaxation (Moser et al, 2004;Lundervold & Poppen, 2004), compliance enhancement training, thermal bio-feedback (Somers et al, 2005), behavioural education processes (Moss et al, 1991), exercise, cognitive behaviour therapy (Sheps et al, 2003), yogic breathing and meditation intervention (Brazier et al, 2006). Bio-behavioural models and analyses have been used to explain cancer stress and disease course, headache and hypertension (Schwartz et al, 1979).…”
Section: Methodsmentioning
confidence: 99%
“…Interventions through changing the behavioural aspects, like relaxation, adherence to medication, compliance enhancement, bio-feedback techniques, health behaviour practices, exercise, etc., have been carried out to measure its effect on the biological parameters and patho-physical mechanisms (e.g., cardiovascular mechanisms, weight control, cortisol level, immune parameters, etc.). Bio-behavioural interventions have used different behavioural and cognitive nonpharmacologic techniques, like bio-feedback, relaxation (Moser et al, 2004;Lundervold & Poppen, 2004), compliance enhancement training, thermal bio-feedback (Somers et al, 2005), behavioural education processes (Moss et al, 1991), exercise, cognitive behaviour therapy (Sheps et al, 2003), yogic breathing and meditation intervention (Brazier et al, 2006). Bio-behavioural models and analyses have been used to explain cancer stress and disease course, headache and hypertension (Schwartz et al, 1979).…”
Section: Methodsmentioning
confidence: 99%
“…No clinically important benefits were apparent in two small trials of psychosocial support11 (80 women) or biobehavioural training12 (45women). Data do not allow for reliable conclusions to be drawn about the benefits and risks of restricted activity with or without admission to hospital for mild hypertension later in pregnancy.…”
Section: Hypertension In Later Pregnancymentioning
confidence: 98%
“…A later randomized controlled trial ( n = 50) of biofeedback plus relaxation with guided imagery and self‐monitoring of blood pressure, versus education to enhance compliance with bedrest, or bedrest (usual care) for pregnant women with hypertension found that mean arterial pressure at the last prenatal visit before delivery increased in both the education and control groups, compared with baseline, and significantly decreased in the intervention group ( F [1, 28] = 7.18, p < 0.025). The experimental group also had significantly lower absolute blood pressure when compared with the other groups ( F [2, 42] = 9.30, p < 0.001), but actual blood pressure values were not reported (22). However, many relaxation techniques require an extended time to learn (12), and thus may not be ideal for use during pregnancy.…”
mentioning
confidence: 99%